MODIFIED CONCRETE SEWER PIPE COLLECTORS (Municipal economy of cities. Series: «Economy science», 2013)
The results of the research , the purpose of which is to provide a corrosion-resistant concrete for products that are operated in a corrosive environment of different nature. <span title="Разработанная технология изготовления коррозион-ностойких бетонных труб для канализационных коллекторов основана на сочетании виброударно-импульсного уплотнения бетонной смеси и снижения действительного водоцементного отношения в отформованном бетоне до уровня, равного нормальной густоте цементного теста.">The developed technology of corrosion nostoykih concrete pipe for sewers is based on a combination of vibro -pulse sealing of concrete and reduce the actual water-cement ratio in the molded concrete to a level equal to the normal density of the cement paste.